Perspectives on pharmacy access to hormonal contraception among rural New Mexico women - Lauren Thaxton; Elizabeth Clark; Jocelyn Aubrey Wu; Alexandra Herman; Andrew L. Sussman; Eve Espey (Elsevier, 2021)
Objective: In 2017, New Mexico approved an amendment allowing pharmacists to prescribe and dispense hormonal contraception. We interviewed rural New Mexico women to determine their perceptions of pharmacy access to hormonal contraception. Study design: We conducted semi-structured telephone interviews with women recruited from rural New Mexico communities. The interview guide explained the amendment followed by questions about the advantages and disadvantages of pharmacy access to hormonal contraception within rural communities. Results: Between November 2017 and May 2018, we recruited 32 women to participate. Participants were young (26/32 18-29 years old), gravid (27/31), employed (30/32), white (22/32) and Hispanic (26/31). The majority used Medicaid as their primary insurance (16/28). Most participants were supportive of pharmacy access to hormonal contraception. Participants saw their rural communities as facing health care barriers, some of which could be alleviated by pharmacy access. Perceived benefits of pharmacy access included convenience of pharmacy hours, shorter wait times, and no need for an appointment. Participants expressed concerns about lack of privacy in their pharmacies. Many expressed trust in their pharmacist to review side effects and explain usage of contraception- a role that was considered separate from that of a primary care provider who offers regular medical visits for routine screening and nuanced or complex discussions about contraception. Some participants expressed that pharmacy access could be especially beneficial for teens. Conclusions: Rural New Mexico women were supportive of pharmacy access to contraception and accept pharmacists as trusted members of the health care team. Implications: Rural New Mexico women find benefit in pharmacy access to hormonal contraception, citing improved access to contraceptives in their communities.